N‐Doped Carbon‐Coated Ni1.8Co1.2Se4 Nanoaggregates Encapsulated in N‐Doped Carbon Nanoboxes as Advanced Anode with Outstanding High‐Rate and Low‐Temperature Performance for Sodium‐Ion Half/Full Batteries - Hou, Bao‐Hua; Wang, Ying‐Ying; Liu, Dao‐Sheng; Gu, Zhen‐Yi; Feng, Xi; Fan, Haosen; Zhang, Tuofeng; Lü, Changli; Wu, Xing‐Long (Advanced functional materials, 2018)
Transition metal selenides have been attracting significant attention owing to their high conductivity and theoretical capacity. In this article, the N‐doped carbon (NDC)‐coated Ni1.8Co1.2Se4 nanoparticles encapsulated in NDC nanoboxes are prepared from the bi‐metal organic framework (Ni3[Co(CN)6]2·6H2O, Ni‐Co BMOF) after the selenization reaction and carbon coating. When used as an anode material for sodium‐ion batteries, the prepared anode material delivers excellent rate performance (211 and 153 mA h g−1 at ultrahigh current densities of 30 and 50 A g−1, respectively) and good cycling performance (379.3 mA h g−1 at 0.5 A g−1 after 100 cycles). More importantly, it also exhibits superior sodium‐ion full cell (SIFC) performance when coupled with a high‐voltage Na3V2(PO4)2O2F cathode recently self‐made by the authors. The fabricated SIFC gives an energy density up to 227 W h kg−1 and the capacity retention of above 97.6% even after 60 cycles at 0.4 A g−1 in a voltage range of 1.2–4.3 V at 25 °C. Moreover, the low‐temperature (from 25 to −25 °C) Na‐storage performance of the fabricated SIFC is also studied. An advanced anode material with outstanding high‐rate and low‐temperature properties is developed for sodium‐ion half/full batteries. In it, there exists a 3D conductive network composed of N‐doped dual carbon (NDDC) and abundant void spaces between NDDC and Ni1.8Co1.2Se4 nanoparticles, acting as not only a highway to achieve fast charge transfer but also an effective protector for active Ni1.8Co1.2Se4 material.